DEEP READING AND COGNITIVE DEVELOPMENT IN THE DIGITAL AGE – CHALLENGES AND EDUCATIONAL STRATEGIES - Udovychenko, Larysa (The Modern Higher Education Review, 2025)
This article examines the cognitive, neuropsychological, and pedagogical significance of deep reading in the context of the digital transformation of contemporary culture. Drawing on interdisciplinary research in neuroscience, cognitive psychology, media studies, and reading pedagogy, the study defines reading as a complex cognitive activity that integrates visual, linguistic, semantic, and affective processes. Such integration strengthens executive functions, sustained attention, metacognitive monitoring, analytical reasoning, and social and emotional competencies. A theoretical analysis of recent empirical findings reveals substantial evidence that digital environments – characterised by fragmentation, accelerated media formats, and habitual multitasking – undermine the cognitive conditions necessary for deep reading. International assessments such as PIRLS and PISA likewise indicate a decline in reading stamina, comprehension depth, and higher-order interpretive skills among school-age learners. These tendencies are exacerbated by the persistence of outdated instructional models that emphasise factual reproduction rather than immersive engagement with literary texts. The study argues that restoring deep reading requires a pedagogical reorientation toward slow, reflective, and emotionally engaged interaction with texts, supported by teachers who understand the cognitive mechanisms of reading and the challenges of digital culture. Policy-level measures, including curriculum redesign and strengthened reading promotion initiatives, are also essential. Overall, the article demonstrates that deep reading remains a vital cognitive and cultural practice capable of fostering intellectual resilience, ethical sensitivity, and reflective thinking in the digital age.